KERJASAMA INDONESIA – ARGENTINA DALAM BIDANG ASSURANCE OF PRODUCT HALAL TAHUN 2021-2023 - Ardi, Andre; Tania, Risa (Universitas Prof. Dr. Moestopo (Beragama), 2023)
This research aims to analyze Indonesia - Argentina cooperation in the field of assurance of halal products in 2021-2023. The research method used is a qualitative method. The data collection technique is from literature study in the form of books, journals and websites. In this research, the theories or concepts used include National Interest, International Trade, Trade Protection, and Halal Products which will provide understanding of this cooperation. This collaboration can encourage the exchange of knowledge and technology between Indonesia and other countries.